2012
DOI: 10.1187/cbe.11-08-0068
|View full text |Cite
|
Sign up to set email alerts
|

Using Science Songs to Enhance Learning: An Interdisciplinary Approach

Abstract: Music is recognized as an effective mode of teaching young children but is rarely used in university-level science courses. This article reviews the somewhat limited evidence on whether and how content-rich music might affect college students' understanding of science and offers practical suggestions for incorporating music into courses. Aside from aiding memorization, songs may potentially improve learning by helping students feel relaxed and welcome in stressful settings, engaging students through multiple m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 29 publications
(34 reference statements)
1
29
0
8
Order By: Relevance
“…For example, the quadratic formula has been set to the tune of many songs and many mathematical topics have been covered using the lyric '100 Bottles of Beer' [3]. Instructors can find an appropriate method and level for students to analyse or create lyrics in their courses [10,26].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the quadratic formula has been set to the tune of many songs and many mathematical topics have been covered using the lyric '100 Bottles of Beer' [3]. Instructors can find an appropriate method and level for students to analyse or create lyrics in their courses [10,26].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study with students enrolled in this same physiology course, we found that six out of 10 students preferred multiple types of learning, with nearly 70% of the class having kinesthetic or hands-on learning among their preferences (Breckler et al ., 2009). Others have found that multisensorial or multidimensional learning, through the use of music (Last, 2009; Courey et al ., 2012; Crowther, 2012;), audio podcasts (Hancock and Fornari, 2012), or video clips (Kolikant and Broza, 2011) definitely helps engage students in science or math concepts. In any case, a variety of different kinds of presentations of the same material clearly helps excite students and reinforce learning.…”
Section: Discussionmentioning
confidence: 99%
“…, 2012; Cox-Paulson et al. , 2012; Crowther, 2012). Others, in contrast, seemed to use the term to reflect an ad hoc mistake or error in student understanding, one that exists prior to or emerges through instruction but, in either case, is not robust, nor does it interfere with learning (Jenkinson and McGill, 2011; Klisch et al.…”
Section: The Use Of the Term Misconceptions In Current Ber Literaturementioning
confidence: 99%
“…, 2012). The authors who considered misconceptions to be “deeply rooted” spoke of instructional strategies designed to specifically elicit, confront, and replace students’ incorrect conceptions (i.e., Crowther, 2012). In contrast, authors for whom misconceptions were more tentatively held and/or emergent, suggested that students’ incorrect ideas can be amended through tailored instruction grounded in those ideas (i.e., Klisch et al.…”
Section: The Use Of the Term Misconceptions In Current Ber Literaturementioning
confidence: 99%